Dual-wavelength filamentation with a fraction of fundamental laser frequency as a wideband THz source. (7th January 2021) - Nikolaeva, I A; Shipilo, D E; Panov, N A; Kosareva, O G
Abstract: We study the generation of terahertz (THz) radiation from a dual-color filament in air for a Ti:sapphire pump and with different wavelengths of the seed pulse using the unidirectional pulse propagation equation (UPPE). The local transient photocurrent model indicates that the most efficient THz generation corresponds to the seed with either halved or doubled pump frequency compared with the other seed frequencies studied. However, UPPE simulations reveal the crucial decrease in the effective interaction area of the pump and the seed pulses in the case of lower-frequency seeds, due to the strong diffraction of the seed radiation on the plasma obstacle formed by the pump pulse. As the result, the energy of THz radiation drops from 260 nJ for the double frequency to 7 nJ for the halved one.